FENOMENA ONLINE SHOPPING SEBAGAI GAYA HIDUP DAN STRATEGI PEMBERDAYAAN EKONOMI UMAT ISLAM DI MASA PANDEMI COVID 19 - Ade Faulina (Universitas Islam Negeri Imam Bonjol Padang, 2021)
It’s the second year for covid 19 pandemic and it has brought a lot of change in people life around the world. Nonetheless, Indonesia also feels it. A settle life condition that’s been known for long has to change to adapt and to survive the new situation. From social side, economic, culture, religion education and many more. One of the most significant change and become common nowadays are online shopping. The range of user started from old user to new user who never been used this platform before. The online shop no longer become life style complement, but has become the life style itself. It can be seen from numbers of transaction that online shops have every day from one account. What more interesting is they can place themselves as they wish, weather its producer or consumer on their own account. So, to figure out the whole picture of this new phenomena, the researcher will try to digging this up by using qualitative method and case study method. So in the end we can understand this fenomena from many different angle.